CLIMATE DYNAMICS AND AGRICULTURAL SECTOR PERFORMANCE IN INDONESIA: A PROVINCIAL PANEL DATA ANALYSIS - Rian Hilmawan; Siti Amalia; Farah Diba Muna (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
This study examines the effect of climate dynamics on agricultural sector performance in Indonesia using province-level panel data for the period 2014–2023. Employing panel regression estimations under several specifications, the analysis investigates whether average temperature and rainy-day frequency, as the main climate-related variables, are associated with real agricultural Gross Regional Domestic Product (GRDP), which captures the market value in the food and horticultural crop subsectors. The empirical results indicate that temperature is the most robust climate-related predictor of agricultural GRDP across model specifications. By contrast, the effect of rainy-day frequency is more sensitive to the inclusion of year fixed effects, suggesting that rainfall-related effects may be influenced by common annual shocks or broader time-specific conditions. Population is generally positively associated with real agricultural GRDP, although its magnitude weakens after accounting for year effects. Overall, the Driscoll–Kraay estimations confirm that temperature remains a consistent predictor of agricultural GRDP, while the estimated effects of rainy days, land cover, and population are more dependent on model specification, particularly the treatment of year fixed effects.